Tax harmonization in the European community: Problems and prospects - Peter Birch Sörensen (Bank of Finland, 1990)
The paper surveys the plans for tax harmonization in the European Community, including the most recent proposals from the EC Commission. The first part deals with indirect taxation, while th"e second part of the paper focusses on income taxation, with special emphasis on taxes on capital income. The plans for harmonization are critically evaluated, both from a theoretical and from an. administrative point of view. It is argued that complete harmonization of indirect tax rates within the EC is not needed to reap the economic benefits of the InternaI Market. On the other hand, there is a strong case for improved international coordination of capital income ta xes , if the potential benefits of a liberalized international capital market are to be realized.
URN:NBN:fi:bof-201807311790
Keywords: 330